2021
DOI: 10.3390/children8040257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of a Neonatal Care Bundle for the Prevention of Intraventricular Hemorrhage in Preterm Infants

Abstract: Germinal matrix intraventricular hemorrhage (IVH) remains a severe and common complication in preterm infants. A neonatal care bundle (NCB) was implemented as an in-house guideline at a tertiary neonatal intensive care unit to reduce the incidence of IVH in preterm infants. The NCB was applied either to preterm infants <1250 g birth weight or <30 weeks gestational age or both, and standardized patient positioning, nursing care, and medical procedures within the first week of life. A retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
2
4
0
2
Order By: Relevance
“…Our findings are in keeping with the study by Gross et al [41] who evaluated the effectiveness of a neonatal care bundle similar to our "brain protection bundle" to reduce the rate of IVH and failed to demonstrate any difference in the overall and severe grades of IVH. However, they are in contrast to several other quality improvement (QI) studies that have targeted initiatives to reduce IVH or short-term neonatal outcomes with varying degrees of success [22][23][24][25] Schmid et al demonstrated that the introduction and prospective monitoring of bundle of care practices developed on the basis of risk factors reduced the overall rate of IVH (from 22.1 to 10.5%) and severe IVH (from 9.1 to 3.7%) over a period of 23 months.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in keeping with the study by Gross et al [41] who evaluated the effectiveness of a neonatal care bundle similar to our "brain protection bundle" to reduce the rate of IVH and failed to demonstrate any difference in the overall and severe grades of IVH. However, they are in contrast to several other quality improvement (QI) studies that have targeted initiatives to reduce IVH or short-term neonatal outcomes with varying degrees of success [22][23][24][25] Schmid et al demonstrated that the introduction and prospective monitoring of bundle of care practices developed on the basis of risk factors reduced the overall rate of IVH (from 22.1 to 10.5%) and severe IVH (from 9.1 to 3.7%) over a period of 23 months.…”
Section: Discussionsupporting
confidence: 91%
“…This was confirmed by Yeo, et al, (2020), who stated that early gestational age and low birth weight increase the risk of IVH in preterm infants. These findings are consistent with findings from various other studies (Gross, et al, 2021;Kolnik, et al, 2023).…”
Section: Table (6)supporting
confidence: 94%
“…A review of studies published in 2021 not included in our meta-analysis reported a wide range of incidences and GA inclusion criteria, demonstrating the significant heterogeneity in the literature: any IVH 13%–40% for GA 28–29 weeks,23 24 27% for GA <30 weeks,25 25%–29% for GA <32 weeks,23 12% for GA <34 weeks26 and 2% for GA 34–35 weeks;27 sIVH 29% for GA 22–24 weeks and 9% for GA 25–28 weeks,28 15%–29% for GA <32 weeks29 30 and 4% for GA <34 weeks 26. A systematic literature review of global incidence of sIVH between 2006 and 2017 ranged from 5% to 52% (our 95% CI for this age group was 13% to 17%) with the majority of studies reporting incidence <20% 7…”
Section: Discussionmentioning
confidence: 95%